2000
DOI: 10.1111/j.1572-0241.2000.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 13C-urea breath test for the diagnosis of helicobacter pylori infection in children: a multicenter study

Abstract: The 13C-UBT is an accurate test for the detection of H. pylori infection also in children. Administration of 50 mg of 13C-urea, a fatty test meal, and breath sampling at 30 min appears to be the most convenient protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 14 publications
2
59
1
Order By: Relevance
“…In this review, five different measuring equipments were used. Eighteen of 28 papers used the traditional isotope ratio mass spectrometer [4,11,18,21,24,30,36,48,51,60,79,86,92,106,119,122,124,127].…”
Section: C-urea Breath Testmentioning
confidence: 99%
“…In this review, five different measuring equipments were used. Eighteen of 28 papers used the traditional isotope ratio mass spectrometer [4,11,18,21,24,30,36,48,51,60,79,86,92,106,119,122,124,127].…”
Section: C-urea Breath Testmentioning
confidence: 99%
“…The stool test based on monoclonal antibodies has proved to be highly accurate in all age groups (13)(14)(15), but the specificity of the [ 13 C]UBT varies from 82% to 100% for young children (9)(10)(11)(12). However, studies of this subject are scarce and have not included large enough numbers of infants and toddlers to obtain reliable results.…”
mentioning
confidence: 99%
“…The noninvasive [ 13 C]urea breath test ([ 13 C]UBT) (9)(10)(11)(12) and stool antigen test (13)(14)(15) are very reliable for the diagnosis of H. pylori infection in children older than 6 years. The stool test based on monoclonal antibodies has proved to be highly accurate in all age groups (13)(14)(15), but the specificity of the [ 13 C]UBT varies from 82% to 100% for young children (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] These studies have shown that the UBT is reliable for detecting H. pylori infection. However, reports on the role of the UBT in the assessment of eradication therapy and in the followup evaluation of patients post-treatment have been relatively few.…”
Section: Introductionmentioning
confidence: 99%